Language maintenance and shift in multilingual ecologies: a case study of ethnic minorities in Yunnan - Yu, JianBin; Ng, Boon Sim; Mamat, Roslina (Sciedu Press, 2024)
This study aimed to address the process of language maintenance and language shift in multilingual ecologies, specifically the ethnic minority communities of Yunnan province, China. The research covers a study on Chinese communities carried out in the Yunnan Region with an emphasis on language shift, language ecology, and language preservation. The language environment is becoming more and more multilingual. The smaller language groups have been overlooked in favour of the larger competing languages in earlier research on the linguistic dynamics in Yunnan. By looking at language competency levels, usage patterns, and skill sets among Chinese communities, this paper seeks to correct this omission. Through the integration of language ecology approaches with analyses of language preservation and transition, as well as the use of questionnaire data, we investigate the impact of evolving sociodemographic factors on language retention and change in the context of larger Chinese communities.In this study, Data regarding linguistic habits were gathered by a questionnaire survey, skill levels, and repertoires within these communities. As part of the research approach, sociolinguistic background data, language repertoires, language usage patterns, and attitudes towards various languages were all examined. The study utilized qualitative data that was collected through semi-structured interviews through zoom, participant observation and language analysis. The research illustrated the dynamic relationship between individual agency and social cause that shape language attitudes and behaviors of different actors. The findings would help to develop understanding of linguistic diversity in China and other contemporary multilingual settings and find ways to support language revitalization and an equal and inclusive language policy. The research implies that language change on the formation of individual, group and collective identity, social cohesion within a community, and cultural heritage preservation.